Dietary intake of vitamin B12 in relation to diet and lifestyle characteristics in a population at high risk for colorectal cancer - Banjari, Ines; Kožić, Snježana (Central European journal of public health, 2018)
OBJECTIVE: Besides irreplaceable role in health, vitamin B12 is proposed to have cytoprotective role in colorectal cancer (CRC). So far, studies are inconclusive on the role dietary intake of vitamin B12 has in CRC. The aim of this study was to determine whether total dietary intake of vitamin B12 and contribution from its food sources relates to a low-risk diet and lifestyle in a population at high risk for CRC. METHODS: An observational study on 200 healthy adults from Eastern Croatia was conducted during April-May 2013. A typical diet of this population in this region is characterized with all known major dietary risk factors for CRC placing the population at high risk for CRC, yet the incidence of CRC remains relatively low. RESULTS: Diet and lifestyle characteristics of 52.2% of participants can be classified as the high-risk for CRC. Women, people in lower BMI category, and urban residents have significantly lower risk of the high-risk diet and lifestyle. Higher intake of vitamin B12 shows positive association with the low-risk diet and lifestyle. Intake of vitamin B12 from milk, dairy and fish represent independent factors for the low-risk diet and lifestyle in this population at high-risk for CRC. CONCLUSIONS: Higher intake of vitamin B12, especially intake from milk, dairy and fish are associated with the low-risk diet and lifestyle in a population at high risk for CRC. Further studies should focus on interplay between vitamin B12 and other nutrients that share the same food sources to elucidate their role in the aetiology and pathology of CRC.
Keywords: Vitamin B 12; dietary vitamin B12; diet and lifestyle characteristics; Humans; Croatia; Diet; vitamin B 12; Female; rizikové faktory; dospělí; lidé; Chorvatsko; Adult; colorectal cancer; ženské pohlaví; kolorektální nádory; Life Style; životní styl; Male; dieta; population at high-risk for CRC; mužské pohlaví; high-risk diet and lifestyle; Colorectal Neoplasms; Risk Factors